Diastereoselective construction of spirocyclic isobenzofurans via a tandem Michael addition/5-exo-dig cyclization reaction - Mehdidoust, Shaghayegh; Rajai-Daryasarei, Saideh; Hosseini, S. Sina; Rominger, Frank; Bijanzadeh, Hamid Reza; Balalaie, Saeed; Ramezanpour, Sorour (The journal of organic chemistry, 2024)
A practical approach for rapid and efficient access to spirocyclic isobenzofurans is described. The reaction proceeds through the cycloaddition of 1,6-ynenone derivatives and 4-nitro-1,3-diarylbutan-1-ones, promoted by Cs2CO3 in the presence of l-proline as a catalyst. The advantages of this reaction include the formation of two C-C bonds and one C-O bond as well as mild reaction conditions. Extended spirocyclic isobenzofurans are obtained with good efficiency and diastereoselectivity under these mild conditions, and this new protocol avoids the use of any transition-metal reagents.